Multi-criteria optimization of lateral load-drift response of posttensioned steel beam-column connections. (1st January 2017) - Moradi, Saber; Alam, M. Shahria
Highlights: Optimal regions are found for each factor using a desirability approach. Connections with deeper beams and higher posttensioning forces exhibit early damage. Dominant limit state for the posttensioned (PT) connections is beam local buckling. No strand yielding if initial PT force is less than 50% of strand ultimate strength. High strength A490 bolts of 32 mm diameter are adequate for use in PT connections. Abstract: Posttensioned (PT) elements in steel buildings can substantially mitigate permanent seismic damages and the associated post-earthquake repair costs during earthquakes. In this paper, a response surface methodology (RSM) is used to predict and optimize the lateral response characteristics of PT steel beam-column connections with top-and-seat angles. The monotonic lateral response characteristics considered in the study include: initial stiffness, load capacity, and ultimate drift of PT connections, as well as load and drift levels corresponding to the gap-opening (decompression) in PT connections. Based on the results of finite element simulations and extensive sensitivity studies, six influential parameters are considered as input variables in this study. These parameters are posttensioning strand force, beam depth, beam flange thickness and width, span length, and column height. By using a desirability approach, the lateral response of PT steel beam-column connections is optimized. The optimization studies aim at maximizing the initial stiffness, load capacity, and ultimate drift of PT connections and/or minimizing the amount of steel in the beam section, which contributes to the final cost of frame structures. The multi-criteria optimization studies reveal the regions of factor space where optimal conditions are achieved. The optimized solutions are then confirmed by performing simulation runs with the optimal factor combinations. Among the results, it is shown that damage occurs earlier in PT connections with deeper beams and greater posttensioning strand forces. The dominant limit state for the PT connections was beam local buckling starting at early drifts of 1.2%, whereas the first occurrence of angle fracture was at about 4% drifts, and two limit states of strand yielding and bolt extensive yielding were not observed in the analyzed PT connections.